2016
DOI: 10.4236/ajps.2016.712149
|View full text |Cite
|
Sign up to set email alerts
|

<i>In-Silico</i> Analysis & <i>In-Vivo</i> Results Concur on Glutathione Depletion in Glyphosate Resistant GMO Soy, Advancing a Systems Biology Framework for Safety Assessment of GMOs

Abstract: This study advances previous efforts towards development of computational systems biology, in silico, methods for biosafety assessment of genetically modified organisms (GMOs). C1 metabolism is a critical molecular system in plants, fungi, and bacteria. In our previous research, critical molecular systems of C1 metabolism were identified and modeled using CytoSolve ® , a platform for in silico analysis. In addition, multiple exogenous molecular systems affecting C1 metabolism such as oxidative stress, shikimic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
1
1
0
1
Order By: Relevance
“…In our study, the single variety showed a decrease in the light-harvesting chlorophyll A and B contend (complex I of class LhcA 2,3 and 4 with four genes involved, and the complex II of class LhcB 1,2,3 and 6 with nine genes involved). These findings are supported by Li et al [102], who also observed a decline in the content of chlorophyll A and B in GM and conventional soybean varieties under glyphosate treatment [102].…”
Section: Photosynthesis Imbalancesupporting
confidence: 61%
“…In our study, the single variety showed a decrease in the light-harvesting chlorophyll A and B contend (complex I of class LhcA 2,3 and 4 with four genes involved, and the complex II of class LhcB 1,2,3 and 6 with nine genes involved). These findings are supported by Li et al [102], who also observed a decline in the content of chlorophyll A and B in GM and conventional soybean varieties under glyphosate treatment [102].…”
Section: Photosynthesis Imbalancesupporting
confidence: 61%
“…Oxidized glutathione (GSSG) is reduced to GSH by NADPH generated by G6PDH in the pentose phosphate pathway [64]. Complete depletion of glutathione in its reduced form (GSH), or the production of GSSG from GSH, with concomitant accumulation of formaldehyde have already been reported as signs of undergoing oxidative stress in single-transgene soybean event as compared to its non-GM isogenic line [19,65].…”
Section: Altered Cellular Redox Homeostasismentioning
confidence: 99%
“…Refs. [ 49 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ] are cited in supplementary materials.…”
unclassified